Determinants of Purchase Decisions among E-commerce Users: The Significance of Trust, Security, Price, Service Quality, and Risk Perception - Muhammad Rizkan; Nur Faiza; Muhammad Akbar; Nursani (LPPM Universitas Negeri Jakarta, 2023)
The objective of this study is to determine the influence of Trust, Security, Price, Service Quality, and Risk Perception on Purchase Decisions of E-commerce users through Shopee. This is a quantitative study using a data collection technique of a questionnaire distributed through Google form with a sample size of 100 respondents processed with SPSS version 23. The data analysis uses multiple linear regression. The results of the hypothesis test show that: (1) trust affects purchase decisions; (2) security affects purchase decisions; (3) price does not affect purchasing decisions; (4) service quality does not affect purchasing decisions; and (5) risk perception affects purchase decision of E-commerce consumers through the Shopee website.Trust